Analysis Of Recent Research In Solketal Synthesis Toward Circular Economy : A Review - Adna Ivan Ardian; Tamaratritania Citta Trisnantari; Dennis Farina Nury; Rizky Ibnufaatih Arvianto; Suhirman Suhirman (Program studi Teknik Kimia UNS, 2026)
Indonesia’s growing biodiesel production has caused a large surplus of crude glycerol, which becomes both an economic and environmental problem. The study present a systematic chemical engineering perspective on how glycerol can be transformed into solketal, a compound that can act as a biofuel additive and green solvent. The discussion is based on a systematic reading method of twelve research papers published between 2018 and 2024, specifically discuss the development of catalysts related to this process. The contrasting performance between catalyst efficiency and its industrial implementation become a concern. It shows Zeolites and MOF catalyst exceed other types of catalysts by using process intensification in laboratory. But in contrast, their stability lower when associated with impurities found in feedstock, followed by heat-related problems. On the other side, simple and cheaper catalysts such as acid-treated clays still show steady activity even in less clean feedstocks, making them more realistic for larger scale operation. The review also points out that improving catalyst lifetime and using new process approaches like microwave heating are important to make the process more economical. Overall, this study suggests that creating catalysts which can resist impurities together with better process design is necessary to make glycerol utilization more sustainable and in line with Indonesia’s circular economy plan.